Assessment on the mechanical, structural, and thermal attributes of green graphene‐based water soluble polymer electrolyte composites. Issue 7 (16th August 2019) - Sultana, Sabiha; Bhatti, Haq Nawaz; Yasmin, Farah; Khan, Abdul Naeem; Rehan, Imran; Rehan, Kamran; Noor‐ul‐Amin,
ABSTRACT: In the current study, graphene oxide (GO) was prepared using green chemistry with modified Hummer's method without incorporating sodium nitrate (NaNO3 ). Solvent casting was employed to fabricate GO‐doped poly(ethylene oxide) (PEO), that is, PEO/GO composites with various proportion of Na2 SO4 and were then subjected to characterization via advanced spectroscopic techniques for different physicochemical aspects to estimate their potential applications as marketable products. XRD analysis explored that fabricated composites are more crystalline than neat PEO. PEO/GO/Na2 SO4 composite films offered maximum crystallinity. SEM displayed the same trend. TG/DTA thermogram exposed better thermal stability than pristine polymer. FTIR studies confirmed complexation among hybrid's components. Elongation‐at‐break and Young's modulus displayed an enhancing behavior with an incremental loading of salt and filler. In terms of mechanical performance, composite of PEO with 0.37 wt % GO and 0.08 g salt was found to be an ideal composition during the course of study. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48376. Abstract :